TASAWUF TUMBUH DI NEGERI SINGA : Reaksi Terhadap Ahl Tareqat - Yola, Nilma; Putranti Rahmaning Tiyas, Diah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Singapore, as an Islamic minority country, was once the center for the development of Islamic scholarship in Southeast Asia. Singapore's position as a center for international trade and commerce has encouraged scientific transmigration from the Middle East to the archipelago, which was spearheaded by traders and Sufis. This serves as the foundation for the presence of Sufism in Singapore. This study aims to explain the history of Islam in Singapore and the development of Sufism there. The approach used in this research is qualitative. The process begins with gathering data and sources pertinent to the conversation. The obtained data and sources undergo verification, which involves review, comparison, and analysis. Once the correct results are obtained, the final stage of the data analysis is documented in written form. According to the study's findings, it is very likely that the arrival of Islam in Singapore occurred from the 8th to the 11th centuries, brought by traders from Arabia. When the Malacca Sultanate controlled Temasik in the 15th century, Islam experienced rapid development. In Singapore, Sufism-style Islam emerged. Despite experiencing ups and downs, the teachings of Sufism are still part of the Islamic tradition in Singapore. As a result, Islam, as a minority religion, was able to survive until it finally had various legitimate institutions in the Singapore government.